Single-parent immigrant families in Iceland : lives and educational experiences of their children - Fuhui Chen 1986- (2013)
Literature concerning immigration or single-parenting respectively is abundant, but there is limited research on single-parent immigrants in Iceland. Therefore, it is useful to research how single-parent immigrants support themselves and their children in Iceland, and to understand their experiences of their children’s education. The aim of this study is to explore what situations immigrant single-parent families face in Iceland, and how they cope with the integration process. This is a qualitative interview study where 11 participants are recruited through a purposive sampling strategy for semi-structured in-depth interviews to collect data. The main significance of this study is to understand the experiences of individuals during the process of integration into the society and their efforts to support themselves and their children in Iceland. The study thus gives a minority group a voice while also providing important information for Icelandic society and educational system. Findings of this study show that these immigrant single parents have not had very difficult integration experiences in Iceland, but most of them cannot speak Icelandic fluently, so they have some problems in getting access to necessary information. All the immigrant single parents in this study can support their families with their salary and the financial support from the state. According to the findings of this study, it is clear that the work-family conflict is alleviated by the financial and social support system. All the immigrant single parents interviewed in this study are concerned about preserving their children’s mother tongue, but all of them put their first consideration on their children’s Icelandic language learning. Discontinuities between home and school are also discovered in this study. Most children in this study experienced marginalization in Icelandic schools, particularly in the first few months of attending the schools, when they were rejected by groups of Icelandic children. Ýmsar rannsóknir er varða innflytjendur ...